Mutu Pelayanan Radiologi Di Balai Besar Kesehatan Paru Masyarakat (BBKPM) Makassar - Salam, Nurbeti; Ariyanto, Bambang; Gayatri, Maharani (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2021)
Services in the field of radiology which are health support services also need to maintain and improve the quality of their services. Radiology is one of the supporting units of health services in establishing the diagnosis of a disease and also needs to maintain and improve the quality of services appropriately and safely, both for patients (users), radiographers (officers) and the community or the surrounding environment. This study aims to determine the quality of radiology services at the Center for Community Lung Health (BBKPM) Makassar. The method used is descriptive research with a quantitative approach. The population is all patients in the radiology installation of the Center for Community Lung Health (BBKPM) with a sample of 158 people. The results showed that the quality of radiology services in terms of timeliness was categorized as very high, namely 91.86%. The cost of Thorax photo examination services is relatively cheap and affordable and the service waiting time reaches a fairly high-quality value of 86.79%. The information aspect reached a high-quality value, namely 85.97%. The technical executor of the Thorax photo examination is carried out by a radiographer and the executor of the diagnostic results is a radiologist (radiology specialist) who has achieved a fairly high-quality score of 97.15%. Aspects of Human Relations have reached a fairly high-quality score of 87.00%. Environmental Aspects achieved a quality value of 97.57%. It is recommended that the Makassar BBKPM management provide a complaint box (suggestion box) in the radiology room to evaluate services.